2009
DOI: 10.1159/000256659
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1-Induced Epithelial-to-Mesenchymal Transition and Therapeutic Intervention in Diabetic Nephropathy

Abstract: Background/Aims: Epithelial-to-mesenchymal cell transformation (EMT) is the trans-differentiation of tubular epithelial cells into myofibroblasts, an event underlying progressive chronic kidney disease in diabetes, resulting in fibrosis. Mainly reported in proximal regions of the kidney, EMT is now recognized as a key contributor to the loss of renal function throughout the nephron in diabetic nephropathy (DN). Concomitant upregulation of TGF-β in diabetes makes this pro-fibrotic cytokine an obvious candidate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
156
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 177 publications
(162 citation statements)
references
References 133 publications
3
156
0
2
Order By: Relevance
“…In addition, its upregulation is a common characteristic of renal tubulointerstitial fibrosis in DN. 20 In this study, we first found that the mRNA and protein expression of FN, ColIV, and TGF-b1 was upregulated with HG stimulation, whereas NCTD could evidently inhibit their upregulation in a time-dependent manner. Because TGF-b1 can increase ECM protein synthesis, including ColIV and FN, we suggested that NCTD might downregulate FN and ColIV expression in HK-2 cells induced by HG through inhibition of TGF-b1 expression.…”
Section: Effects Of Nctd On Can/nfatc Signaling Pathway In Hk-2 Cellsmentioning
confidence: 74%
“…In addition, its upregulation is a common characteristic of renal tubulointerstitial fibrosis in DN. 20 In this study, we first found that the mRNA and protein expression of FN, ColIV, and TGF-b1 was upregulated with HG stimulation, whereas NCTD could evidently inhibit their upregulation in a time-dependent manner. Because TGF-b1 can increase ECM protein synthesis, including ColIV and FN, we suggested that NCTD might downregulate FN and ColIV expression in HK-2 cells induced by HG through inhibition of TGF-b1 expression.…”
Section: Effects Of Nctd On Can/nfatc Signaling Pathway In Hk-2 Cellsmentioning
confidence: 74%
“…28,29 Epithelial-to-mesenchymal transition, a process by which differentiated epithelial cells undergo a phenotypic conversion that gives rise to the matrix-producing fibroblasts and myofibroblasts, is increasingly recognized as an integral part of tissue fibrogenesis after injury. Emerging evidence suggests that TGF-b initiates the transition of renal tubular epithelial cells to myofibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding those mediating signals which regulate deposition of fibrotic material in the interstitium is critical to future identification and development of site specific therapeutics which may alleviate this damage. Central to TIF is tubular epithelial-tomesenchymal transition (EMT), or the transdifferentiation of tubular epithelial cells into myofibroblasts [9][10]. In DN, EMT occurs as cells attempt to evade apoptosis as a consequence of exposure to pathophysiological stimuli [11][12].…”
Section: Introductionmentioning
confidence: 99%